The price-volume relationship of the Malaysian stock index futures market - McGowan, Carl B.; Muhammad, Junaina (Academic and Business Research Institute, 2011)
The objective of this study is to determine the relationship and the causality between the price index and trading volume for both the spot and the next month contracts in the Malaysian stock index futures market and how that relationship changes over time. The daily data of the stock index futures (FKLI) closing price and the daily data of the stock index futures (FKLI) trading volume from December 15, 1995 until December 31, 2003 are used in this study. The data are divided into four sub-periods, a learning period, a crisis period, a recovery period and a stable period, to analyze the variation in activity during the opening of the new market, the Asian financial crisis in 1997-1998, the recovery period after the financial crisis, and a stable period. The findings provide information to allow investors to use the price-volume relationship in both the spot-month and the next-month contracts to speculate or to hedge their portfolios.